2014
DOI: 10.1038/modpathol.2013.83
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic analysis for TFE3 rearrangement in Xp11.2 renal cell carcinoma and alveolar soft part sarcoma: validation and clinical experience with 75 cases

Abstract: Renal cell carcinoma with TFE3 rearrangement at Xp11.2 is a distinct subtype manifesting an indolent clinical course in children, with recent reports suggesting a more aggressive entity in adults. This subtype is morphologically heterogeneous and can be misclassified as clear cell or papillary renal cell carcinoma. TFE3 is also rearranged in alveolar soft part sarcoma. To aid in diagnosis, a break-apart strategy fluorescence in situ hybridization (FISH) probe set specific for TFE3 rearrangement and a reflex du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 52 publications
2
65
0
Order By: Relevance
“…A previous study identified that lncRNA ZNF674-1 was aberrantly expressed in primary NPC tissues; however, the function of lncRNA ZNF674-1 in NPC is yet to be investigated (17). lncRNA ZNF674-1 is situated at chromosomal location Xp11, and is 626 bp (17) and it has been identified that Xp11.2 translocation is closely associated with renal cell carcinoma tumorigenesis (34,35). This indicates that lncRNA ZNF674-1 may be a cancer-associated gene involved the carcinogenesis of NPC.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study identified that lncRNA ZNF674-1 was aberrantly expressed in primary NPC tissues; however, the function of lncRNA ZNF674-1 in NPC is yet to be investigated (17). lncRNA ZNF674-1 is situated at chromosomal location Xp11, and is 626 bp (17) and it has been identified that Xp11.2 translocation is closely associated with renal cell carcinoma tumorigenesis (34,35). This indicates that lncRNA ZNF674-1 may be a cancer-associated gene involved the carcinogenesis of NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a subset of pediatric RCCs show a X;17 translocation, which is typically balanced. 46 These RCCs demonstrate papillary architecture, clear to eosinophilic cytoplasm, and psammoma bodies. 47 Fluorescence in situ hybridization (FISH) probes to differentiate balanced versus unbalanced X;17 translocations have been devised, and may be of use in cases of metastatic disease with unknown primary.…”
Section: Differential Diagnosismentioning
confidence: 98%
“…47 Fluorescence in situ hybridization (FISH) probes to differentiate balanced versus unbalanced X;17 translocations have been devised, and may be of use in cases of metastatic disease with unknown primary. 46 Malignant melanomas with epithelioid morphology can have some overlap with ASPS, but can be differentiated by immunoreactivity for melanocytic markers and lack of PAS-D-positive crystals.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…TFE3 belongs to the MiTF family of transcription factors, which share a common helix-loop-helix leuzine zipper dimerization motif, a transactivation domain and a basic region involved in DNA contact and binding. TFE3 is a fusion partner for multiple other tumors including Xp11 translocation-associated renal cell carcinomas, alveolar soft-part sarcoma and a subset of PEComas [37][38][39]. In all tumors, the bHLH-LZ and transcriptional activation domain of TFE3 is conserved in the fusion and the ultimate outcome is high-level expression of TFE3.…”
Section: Epithelioid Hemangioendotheliomamentioning
confidence: 98%